2008
DOI: 10.1007/s11217-007-9089-4
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Doing Philosophy of Education: The Question of Style

Abstract: This paper explores the practice of teaching philosophy, and particularly philosophy of education, in a higher education context. Starting from a critical discussion of some of the literature on teaching and learning in higher education, I introduce the notions of philosophical style and temperament and suggest that exploring these notions, the problems they raise, and their implications for issues to do with our own identity as philosophers and as teachers, can enrich our understanding of the practice of teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…Moreover, the study results demonstrated that there were positive strong relationship between educational philosophies named liberal, behavioral, progressive, and radical with both expert and facilitator teaching style. This finding in accordance with Suissa (2008) who suggests a direct relationship between educational philosophies and educator teaching style (3) . Moreover, In the Progressive, Unfortunately, few educators consider the implications of their methods or activities (1) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the study results demonstrated that there were positive strong relationship between educational philosophies named liberal, behavioral, progressive, and radical with both expert and facilitator teaching style. This finding in accordance with Suissa (2008) who suggests a direct relationship between educational philosophies and educator teaching style (3) . Moreover, In the Progressive, Unfortunately, few educators consider the implications of their methods or activities (1) .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the educator becomes a philosopher of education when consideration and application of principles occur in classroom processes. Educational philosophies affect educators, curriculum, and learning materials, therefore, it is vital for educators to "engage in a process of examining what they believe and value so that educators will have a clearer sense of where the instruction and learning journey is leading" (1,3) .…”
Section: Educators Should Consider Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…anlaşılmasının güç, oldukça soyut ve karmaşık olması (Bassham ve Austin, 2008;Popkin ve Stroll, 1993;Rosenberg, 1996;Ünsal, 2016 ), uygulama ve pratikten daha çok teorik olması (Bassham ve Austin;Elias ve Merriam;Suissa, 2008) şeklindedir.…”
Section: Felsefe öğRetim Programıunclassified
“…Changes to the practices of teaching philosophy of education, as well as the growing number of sociologically oriented studies in education have provoked ample discussion on methods, tools, "style" and prospects of research in philosophy of education (see, for instance, [Alexander, 2006;Suissa, 2008;Chambliss, 2009;Biesta, 2011;Hayden, 2012]) .…”
Section: Introductionmentioning
confidence: 99%